Pelatihan Perkalian Bilangan Dasar Dengan Metode Jarimatika : Belajar Menjadi Menyenangkan - Reni Wijaya; Dorris Yadewani (Jurnal Pengabdian Masyarakat Akademisi, 2022)
For students elementary school, multiplication is a difficult subject. Whereas multiplication of numbers is the basis of arithmetic operations. This became the background so that this community service activity was carried out with the aim of increasing abilities students' in multiplication counting operations through the application of jarimatika techniques. Methods performed by means of lectures and exercises The first stage begins with the addition material. The second stage is to write the multiplication of 1 to 10 on the board and then answer them together. The third stage is by introducing how to calculate the multiplication of easy numbers starting from multiplying one to ten using fingers. The fourth stage gives participants the opportunity to try to calculate the multiplication of 6 to 10 using the finger method with other participants. The results of this activity make it easy for students to understand multiplication using Jarimatika.